Pengaruh Beban Operasional Terhadap Laba Bersih Pada PT. Bank SulutGo Cabang Gorontalo - Herlambang, Nasrudin (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2024)
The purpose of this study was to determine and analyze the effect of operating expenses to net income at PT. Go Branch of Bank of North Sulawesi Gorontalo. The analytical method used in this study is a quantitative analysis method, using a model of simple linear regression analysis and the source data used in this research is secondary data sources in the form of financial statements issued periodically through anual Report Bank of North Sulawesi Go to the period taken is In 2010 through 2014 in the city of Gorontalo. See the development of the banking world today, the bank is one of the financial institutions who were instrumental in the provision of funds or capital for society or the business world, with different types of loan products both employment and investment as well as other credit products. Based on the partial test results, showing that partial load operations do not significantly affect net income at PT. Go Branch of Bank of North Sulawesi Gorontalo. This is evidenced by the t value 0.385 is smaller than t table 3182 with significant levels biggest t 0726 whose value is greater than 0.05